1999
DOI: 10.1038/sj.onc.1202711
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induced by the myelodysplastic syndrome-associated NPM-MLF1 chimeric protein

Abstract: The NPM-MLF1 chimeric protein is produced by the t(3;5)(q25.1;q34) chromosomal translocation, which is associated with myelodysplastic syndrome (MDS) prior to progression into acute myeloid leukemia (AML). Here we report that K562 human leukemia cells ectopically expressing NPM-MLF1, but not those with wild-type MLF1, were gradually eliminated from the culture by undergoing apoptosis. NIH3T3 mouse ®broblasts engineered to overexpress NPM-MLF1 grew normally but serum deprivation triggered apoptotic cell death w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 44 publications
(30 reference statements)
1
35
0
Order By: Relevance
“…It is possible, likewise, that phosphorylation of the RSXSXP motif in Mlf1 promotes 14-3-3 binding, thereby sequestering the molecule in the cytoplasm and restricting its access to the nucleus. This model is consistent with primary localization of wild-type Mlf1 in the cytoplasm, with small amounts detected in punctate nuclear bodies (1,6,32). Importantly, although the NPM-MLF1 fusion protein is phosphorylated in vivo, it no longer binds 14-3-3 .…”
Section: Discussionsupporting
confidence: 65%
“…It is possible, likewise, that phosphorylation of the RSXSXP motif in Mlf1 promotes 14-3-3 binding, thereby sequestering the molecule in the cytoplasm and restricting its access to the nucleus. This model is consistent with primary localization of wild-type Mlf1 in the cytoplasm, with small amounts detected in punctate nuclear bodies (1,6,32). Importantly, although the NPM-MLF1 fusion protein is phosphorylated in vivo, it no longer binds 14-3-3 .…”
Section: Discussionsupporting
confidence: 65%
“…Notably, co-expression of BCL-2 rescued the fibroblasts from NPM-MLF1-mediated cell death. 49 In summary, we have shown that expression of BCL-2 family proteins and AR differ significantly between ALKϩ and ALKϪ ALCL of T/null lineage, and are not obviously related to PI. These findings further support the concept that ALKϩ ALCL of T/null lineage is a clinicopathological entity, distinct from ALKϪ ALCL, as has been suggested by others.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, NPM-MLF1 is the chimeric product of t(3;5)(q25.1;q34), which is associated with myelodysplastic syndromes. In a recent paper by Yoneda-Kato and colleagues, 49 overexpression of NPM-MLF-1 was capable of inducing apoptosis in NIH3T3 mouse fibroblasts. This induction required the presence of an intact NPM dimerization domain.…”
Section: Discussionmentioning
confidence: 99%
“…The t(3;5)(q25;q34) translocation, seen in one of our patients, rearranges NPM gene with MLF1 gene and related to MDS progression to AML. 22 Translocations involving chromosome 1 were also observed in two cases of der(1;7)(q10;p10), as previously reported in MDS, 23 and in one case with t(1;2)(q21;q37) in our series, in which we identified a new HHL (human hornerin like) gene on 1q21 and showed that its overexpression might be related to MDS/AML transformation (manuscript prepared by YY Wang, SJ Chen et al).…”
Section: Discussionmentioning
confidence: 99%